Association of hippocampal volume with gait variability in pre-dementia and dementia stages of Alzheimer disease : results from a cross-sectional study - Beauchet, Olivier (2020)
Background: Decreased hippocampal volume is a biomarker of Alzheimer disease (AD). The association of hippocampal volume with gait variability across the spectrum of AD, especially in early stages, has been few studied. The study aims to examine the association of hippocampal volume with the coefficient of variation (CoV) of stride time in individuals with mild and moderate to severe subjective cognitive impairment (SCI), non-amnestic mild cognitive impairment (na-MCI), amnestic mild cognitive impairment (a-MCI), and mild to moderate AD dementia. Methods: 271 individuals (79 mild SCI, 68 moderate to severe SCI, 47 na-MCI, 42 a-MCI and 35 mild to moderate AD dementia) were included in this cross-sectional study. Hippocampal volume was quantified from a three-dimensional T1-weighted MRI. CoV of stride time was recorded at self-selected pace with an electronic walkway. Age, sex, body mass index, number of drugs daily taken, history of falls, walking speed, type of MRI scanner, total intracranial volume, and white matter volume abnormality were used as covariates. Results: Participants with moderate to severe SCI had a higher CoV of stride time compared to those with mild SCI and na-MCI (P < 0.010), and a higher hippocampal volume compared to other groups (P ≤ 0.001). Participants with moderate to severe SCI had increased hippocampal volume associated with increased CoV of stride time (coefficient of regression β = 0.750 with P = 0.041), while the other groups did not show any significant association. Conclusions: A positive association between greater hippocampal volume (i.e., better brain morphological structure) and an increased stride time variability (i.e., worse gait performance) in individuals with moderate to severe SCI is reported. This association confirms the key role of the hippocampus in gait control and suggests an inefficient compensatory mechanism in early stages of pathological aging like AD.